Reaction time to peripheral visual stimuli during exercise under normoxia and hyperoxia - Ando, S.; Yamada, Y.; Tanaka, T.; Oda, S.; Kokubu, M. (European Journal of Applied Physiology, 2009)
The purpose of this study was to test if increased oxygen availability affected simple reaction time (RT) to peripheral visual stimuli during exercise. Twelve male participants performed RT tasks at rest, during cycling with three different workloads (100, 150, and 200 W), and after exercise. We fractionated RT into Premotor time and Motor time. Under normoxia, Premotor time significantly increased during exercise at 200 W (mean ± SD, 224.7 ± 34.8 ms) relative to that at rest (213.3 ± 34.1 ms) (P < 0.05). In contrast, we found no difference in Premotor time between at rest (214.0 ± 27.0 ms) and at 200 W (213.0 ± 21.6 ms) under hyperoxia. Furthermore, Premotor time significantly decreased at 150 W (201.3 ± 22.4 ms) relative to that at rest under hyperoxia (P < 0.05). These results suggest that increased oxygen availability during exercise has beneficial effects on perceptual performance.